Mental Health in Team Sports: Etiology, Performance Impact, Barriers, and Interventions - A Literature Review - Brzezicki, Krzysztof; Katarzyna Zegadło; Patryk Jakubiak; Katarzyna Jolanta Kuc; Dominika Krakowiak; Maciej Dobrucki; Kornelia Nieradka (Quality in Sport, 2026)
Background: Elite sports generate extreme stressors (rigorous training, pressure, injuries), causing a high prevalence of common mental disorders, including depression and anxiety. Unfortunately, this topic remains highly stigmatized. Fear of losing contracts or status deters athletes from seeking psychological help, creating a severe treatment gap while prioritizing physical health. Aim of the study: This study comprehensively analyzes mental health challenges in elite team sports. It investigates the etiology of these disorders, their impact on performance and injuries, barriers to help-seeking, and preventive and therapeutic strategies (e.g., load optimization, mindfulness) safeguarding athletes well-being. Material and methods: A comprehensive literature review was conducted to evaluate mental health in elite team sports. The analysis synthesized epidemiological data, psychometric assessments (e.g., POMS), and clinical trials evaluating I-ACT. Data across disciplines, such as basketball and hockey, were examined to identify systemic stressors and underlying biological mechanisms. Results and conclusions: High common mental disorders prevalence in athletes is driven by systemic stressors and injuries. Stigmatization induces a severe treatment gap.Optimal load management, mindfulness, and tailored interventions (I-ACT) are imperative to mitigate distress and safeguard psychological well-being.